Network Pharmacology and Molecular Docking Analysis of Fuzheng Gankang Pill in Treating Combined Allergic Rhinitis and Asthma Syndrome with Lung–Spleen Qi Deficiency and Wind–Cold Invading the Lung Syndrome - Wang, Xin; Pan, Ye; Wang, Suhua; Pang, Zhiyong; Zhao, Zhixin; Yan, Juntao; Dong, Kaiwen; Li, Kun; Zhang, Mingli; Zhang, Junxia (Chinese medicine and natural products, 2025)
To elucidate the mechanism of Fuzheng Gankang Pill in treating combined allergic rhinitis and asthma syndrome (CARAS) with lung–spleen qi deficiency and wind–cold invading the lung syndrome using network pharmacology and molecular docking.The active components and targets of the 13 herbs in Fuzheng Gankang Pill were retrieved from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and HERB. A “core herb-active component–target” network was constructed using Cytoscape to screen core components. CARAS disease targets were obtained from Genecards, National Center for Biotechnology Information (NCBI), and Online Mendelian Inheritance in Man (OMIM). Targets related to the clinical phenotypes of CARAS with lung–spleen qi deficiency and wind–cold invading the lung syndrome were retrieved from the Traditional Chinese Medicine Syndrome Ontology and Multidimensional Quantitative Association Calculation Platform. The intersection of CARAS disease targets and syndrome-related targets yielded CARAS disease–syndrome targets. The intersection of Fuzheng Gankang Pill component-related targets and CARAS disease–syndrome targets provided “disease–syndrome–formula” intersection targets. These targets were uploaded to the STRING database for protein–protein interaction (PPI) network analysis, with topological analysis identifying key targets. Metascape was used for Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Molecular docking validation was performed using AutoDock Vina 1.1.2.The 13 core herbs of Fuzheng Gankang Pill contain a total of 200 active ingredients and 289 related targets. There are 2,412 disease targets for CARAS and 735 corresponding disease targets for the main and secondary symptoms of lung–spleen qi deficiency and wind–cold invading the lung. Through the Venn diagram, a total of 35 intersecting targets were obtained for Fuzheng Gankang Pill, CARAS, and the combination of lung–spleen qi deficiency and wind–cold invading the lung syndrome. Quercetin, Polygonatum sibiricum flavonoids, β-sitosterol, baicalein, kaempferol, etc., are core components. PPI network analysis found that tumor necrosis factor (TNF), prostaglandin-endoperoxide synthase 2 (PTGS2), interleukin (IL)-1β, IL-6, transforming growth factor beta 1 (TGFβ1), BCL2, etc., are the core targets for the compound to exert therapeutic effects. GO enrichment analysis showed that the 13 core drugs of Fuzheng Gankang Pill mainly participate in key biological processes such as positive regulation of protein modification, response to hormones, and negative regulation of cell population proliferation through protein kinases in areas such as membrane rafts, membrane microregions, plasma membrane protein complexes, and receptor complexes. KEGG enriched a total of 30 signaling pathways. Molecular docking shows that active ingredients such as quercetin and kaempferol bind stably to TNF (binding energy ≤ −9.0 kcal·mol−1) and PTGS2 (≤ −8.5 kcal·mol−1).Fuzheng Gankang Pill may regulate biological processes such as cell apoptosis, tissue remodeling, inflammatory response, and immune response by acting on core targets such as TNF and PTGS2 through its core components quercetin, baicalein, β-sitosterol, baicalein, and kaempferol, thereby exerting therapeutic effects on CARAS with lung–spleen qi deficiency and wind–cold invading the lung syndrome.
Keywords: Fuzheng Gankang Pill; CARAS; lung–spleen qi deficiency; wind–cold invading the lung syndrome; network pharmacology; molecular docking